Lightning related effects on the neighborhood of telecommunication tower sites - Chandimal, A. P. Lasantha; Gomes, Chandima

(untitled)
Seventeen communication towers and their neighbourhood have been investigated for lightning threats. There is no credible evidence to conclude that the presence of a tower gives rise to increment of lightning occurrence density or direct strikes to the neighbourhood due to the presence of medium height communication towers. However, there is a realistic risk of step potential hazards and equipment damage in the neighbourhood of the towers due to GPR, transfer of transient through power system and induced effects. It is recommended improving the earthing systems at tower site, transformer and power system of the buildings in the neighbourhood and installing of coordinated system of SPDs at all buildings fed by the transformer. We also emphasize that physical distance to the tower should not be the sole criteria to determine the lightning threats to a building close to a tower. Furthermore, there are many misconceptions among the public on lightning and towers. As these misconceptions may dilute the real issues, the public should be made aware of the scientific background of this scenario.